Q. 11 A3.5( 18 Votes )

# Let S = {a, b, c}

Answer :

(i) It is given that S = {a, b, c} and T = {1, 2, 3}

F : S → T is defined as:

F = {(a, 3), (b, 2), (c, 1)}

= > F(a) = 3, F(b) = 2, F(c) = 1

Therefore, F^{-1}: T → S is given by:

F^{-1} = {(3, a), (2, b), (1, c)}.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

| Let * be a binaMathematics - Board Papers

Find the idMathematics - Board Papers

Let f : A →Mathematics - Exemplar

Show that the binMathematics - Board Papers

Determine whetherRD Sharma - Volume 1

Fill in theMathematics - Exemplar